The carnival in Yoyoy Villame's 18 songs. - Ranoa, Naomi Cielo D. (2006.)
This study explores the carnivalesque structures inherent in the 18 songs of the singer-composer Yoyoy Villame. It aims to examine the "words" in Villame's songs, examine the dominant concepts and symbols in the sogns, and analyze how each song/text relates to the dominant languages as well as the priviledged symbols and concepts. The data needed for this study were gathered trhough the Internet, the reference materials in the Miagao CAS Library, and the interview of the artist by the researcher. To analyze the 18 songs, the reasearche uses Carnivalism, a Russian formalism concept espoused by Mikhail Bakhtin. The findings of this research include faulty grammar, mispronounced words, and invented languages as the main components of Villame's songs. These are problems outright but they nevertheless contribute to the comic nature of his music. As such, the songs are easily remembered by the masses, majority of whom barely reach formal education. The lyrics are also found abundant with concepts and symbols that serve to control the public. they then suggest how ordinary people can have access to these prevailing forces. Finally, the dominant languages, concepts, and symbols in the songs are subverted in unthinkable and funny ways, let alone through the artist's making up of English, Chinese, and Sapnish "words". All these earmarks of his songs carnivalize languages, concepts, and symbols used by the prominent individuals in the society. Like the Carnival they exhibit the anithesis of waht is considered standard, making it available to the commoners. Indeed, novelty songs such as Villame's are not merely entertaining but are fraught with latent meanings as well.
Thesis (Undergraduate, Bachelor of Arts in Literature) College of Arts and Sciences, University of the Philippines Visayas, Miag-ao, Iloilo.
Keywords: Yoyoy Villame's -- Carnivalesque songs